(untitled) (Baghdad Science Journal, 2020)
Abstract: In this study a type of polymeric composites from melting poly propylene as a basic substance with Palm fronds powder were prepared. Evaluation of polymeric composites was done by studying some of it is mechanical properties, which included:Yong modulus (E), Impact Strength (I.S), Brinell hardness (B.H) and Compression Strength (C.S). The polymeric composites were studied before and after reinforcment by comparing between them. There was an increase in resistance of Yong modulus (E), Impact Strength (I.S), Brinell hardness (B.H) and compression Strength (C.S). Also, the effect of some acids were studied such as (HCl, H2SO4, HNO3) with concentrations of (0.5N; 1N and 1.5N) respectively. The physical properties of absorbance and poly propylene’s diffusion coefficient were studied before and after reinforcment, The results showed an increase in values of these properties with increasing concentration of acid and time of polymer’s immersion in the acidic solution.